Implementation of Sports Development Program in Public Elementary Schools - Lasala Jr., Domingo (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study assessed the extent of implementation of the Sports Development Program in selected public elementary schools in the Taytay District, Schools Division Office of Rizal, during the School Year 2025–2026. The study employed a descriptive survey research design and involved two groups of respondents: 94 teacher-coaches and 279 pupil-athletes. Teacher-coaches were profiled in terms of age, sex, civil status, educational attainment, length of service, position, and in-service trainings attended. Pupil-athletes were described according to age, sex, sibling position, family size, monthly income, and parents’ educational attainment and occupation. Data were gathered using a researcher-made questionnaire checklist measuring the extent of program implementation across athlete development, staff development, facilities and equipment, selection of athletes, and administrative support, while also identifying challenges encountered.Findings indicated that teacher-coaches were mostly female, married, aged 31 and above, pursuing graduate studies, with over five years of service, holding the position of Teacher I, and attending various in-service trainings. Pupil-athletes were predominantly aged 10–12 years, male, third or fourth born in families of 2–5 children, with monthly family income above ₱10,000, and parents who were college undergraduates and employed. Both groups perceived the program as highly implemented across athlete development, staff development, selection of athletes, and administrative support, though pupil-athletes noted limited facilities and equipment. Significant differences existed in perceptions regarding staff development and administrative support. Teacher-coaches’ educational attainment influenced their assessment, while pupil-athletes’ demographics did not.The study concluded that effective implementation requires adequate budgeting, prioritization of facilities and equipment, and adherence to a structured action plan. Further studies are recommended to examine additional variables affecting sports program implementation.
Keywords: Sports Development Program, public elementary schools, teacher-coaches, pupil-athletes, program implementation, facilities and equipment